Relação entre as Características Morfológicas e a Qualidade da Cortiça (Silva Lusitana, 2011)
. The main drive of this study was to contribute for a better knowledge about the relationship between the quality of cork and its morphology, aiming to finding out the predictive capacity of the morphological characteristics and their weight to discriminate and select cork quality. Board cork samples were taken out from 9 sample trees (3 trees x 3 sites) and they were prepared to allow quantitative classification according to punctuation classification as described by CARVALHO (1992). Data analysis was done using numerical taxonomy methods. Results generated allow emphasizing that: • The use of punctuation criteria showed the usefulness and significance of some morphological characteristics to segregate cork quality; • Good quality corks were characterized by higher values of the belly's color and low values of the belly’s relief, and its unevenness, and the size and density of the inclusions in the cork mass as well; • Bad quality corks showed a set of dominant morphological characteristics: density, distribution, aggregation and size variation of lenticels and a pronounced relief and also the size of incrustations on the belly; • The introduction of one more parameters – apparent density (DA) – in the morphological analysis did not alter quality classification